Adaption oder Anpassung? Umweltbewusstsein in der Region um den Plattensee/Balaton (Adaptation or a Change in Attitude? Environmental Awareness in the Region of Lake Balaton) - Magdolna Leveleki (DETUROPE)
Over the last decades, climate change has become one of the most relevant issues of modern society. According to the main trends observed in the last decades, it can be concluded that current human efforts are not sufficient to reverse climate change. Therefore, two possible ways of reaction may be envisaged: on the one hand, increasing efforts for prevention and, on the other, preparing for the inevitable changes. As far as the latter is concerned, research on climate change has become a top priority worldwide, as well as, in the European Union, including Hungary. Our sociology working group at Pannon University carried out a research during the years of 2013-2014 related to the social effects of climate change, entitled „Regional effects of extreme weather conditions due to climate change and the possibilities of reducing damage in the upcoming decades”. The Hungarian eco-philopsophical literature highights two main issues concerning the adaptation and a change in values and in attitude related to climate change. The first question is whether we agree with natural scientits, for whom it is undisputed that climate change is caused to a great extent by antropogene effects, and kowing the negative consequences, whether we consider human responsibility in general, and more specifically, our own personal one. The second question is whether a shift in our mindset and in our values is necessary in order to adapt successfully to the new circumstances. If so, what could be the essence of this „paradigm shift” and whether any sign of change can be observed. Our research examined this latter aspect with a special focus on environmental values and attitudes. We have collected empirical data in a region of Eastern-Central Europe that is especially sensitive to the effects of climate change both from an ecological and a social point of view. We compared the results of our research to those of the Eurobarometer and of the Hungarian value sociology. According to our analyses, there are no apparent ecologically desirable changes among the inhabitants of the region of Lake Balaton, and when examining the social differentiation of the trends, one does not find any sign of higher environmental awareness among young people — who, according to Eurobarometer surveys tend to show higher environmental sensitivity. The results of our measures show that the social differences are attributed, therefore, not to age groups, but to the degree of education and to philosophical belief. The questionnaire, which was conducted among the permanent population of the Balaton region also identified a huge gap between the values and the acceptance of the environmentally friendly forms of action. Even though environmental values usually score at the top of the pyramide of values, support for actions aiming at solving environmental problems is not too strong.